'Hour of Code' Demystified. - Ashley, Heather (Education Digest, 2018)
The article discusses the Hour of Code, a series of activities and challenges, in which students are introduced to the world of computer coding every first week of December in various schools. Topics mentioned include the online resource www.code.org which makes the coding simple through a series of tasks and using the blocky drag-and-drop programming, need for teachers to ensure that students work their way down the numerical activity list, and options to choose for coding lesson.